Groundwater Quality Assessment for Drinking Purposes in Budgam Tehsil, Jammu and Kashmir, India - Ganaiee, Younis Ahmad; Dar, Rouf Ahmad; Akbar, Mumin; Marazi, Asif Aziz (Iraqi Journal of Science, 2025)
This study aims to determine the quality of the Groundwater in Budgam Tehsil by using physicochemical parameters. To achieve this objective, groundwater samples were collected from 15 different locations within the study area using a random sampling method from tube wells. The study area was analyzed for various physicochemical parameters, including temperature, electrical conductivity (EC), pH, turbidity, total dissolved solids (TDS), total alkalinity (TA), total hardness (TH), calcium, magnesium, iron, chloride, nitrate, and fluoride concentration. Groundwater suitability was examined by using WHO, BIS, and ICMR standards, which indicates that the quality of groundwater was suitable for drinking purposes. According to this study, all places are within the admissible limit and acceptable for drinking purposes, except for W1, W3, W4, W7, W11, and W15, which require treatment with an oxidizing filter, green-sand filter, or mechanical filter. The higher concentration of Fe may be the result of water’s interaction with the ferromagnesian minerals of the Panjal Trap in the deeper aquifer. Iron can change the taste and color of water, yet in minor amounts, it is not usually damaging to human health. However, high iron levels may encourage the development of particular bacteria in water, which can be detrimental to human health. Based on the findings, the water quality of the analyzed tube wells is fairly good in terms of the monitored elements and physicochemical properties which is safe for drinking purposes and is not expected to pose any substantial health risks to consumers.